2022
DOI: 10.3390/jfb13040266
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of V-Prep Versus Phosphoric Acid Etchant on Oral Gingival Fibroblasts

Abstract: The most used etchant in dental daily practice is the phosphoric acid (P.A.; 37%). However, acid etchants can induce necrosis on the oral mucosa and cause the ulceration of periodontal tissue when a rubber dam is not used. V-prep is a new practical alternative, and it has satisfactory results. It is used as a preparation before the application of a resin-modified glass ionomer composite (RMGIC) to bond the orthodontic brackets. The aim of this study was to investigate the effect of the V-prep on oral gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This study showed comparable results with the conventional composite resin when the enamel surface was prepared with the V-prep and bonded with the Fuji Ortho LC (GC Corporation, Tokyo, Japan) [16]. Another study showed equal or lower toxicity for the V-prep compared to the conventional acid etch when tested on gingival fibroblasts cells for 30 s [17]. Yet, no clinical trial used the V-prep as a preparing agent before the bonding with RMGIC.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This study showed comparable results with the conventional composite resin when the enamel surface was prepared with the V-prep and bonded with the Fuji Ortho LC (GC Corporation, Tokyo, Japan) [16]. Another study showed equal or lower toxicity for the V-prep compared to the conventional acid etch when tested on gingival fibroblasts cells for 30 s [17]. Yet, no clinical trial used the V-prep as a preparing agent before the bonding with RMGIC.…”
Section: Introductionmentioning
confidence: 62%
“…In the latter case, poor results were recorded when comparing the RMGIC to the conventional bonding technique. In this study, the maximum length of monitoring of eighteen months was adopted and a preparation product with reliable in vitro and cytotoxicity results was applied before bonding with RMGIC [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…This is an inevitable shortcoming of this study that focuses only on mRNA expression. Many researchers use primary gingival fibroblast cells from passage 1 to 4 [ 34 37 ]; however, some research groups use cells from later passages [ 38 , 39 ]. A study [ 40 ] that compared the protein expression of gingival fibroblasts, such as IL-6, IL-8, TNF-α and MMP-3, from passage 4 to 5 (early passage cells) compared to passage 30–35 (late passage cells) found no significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…After each etching session, the samples were repolished using the final two colloidal silica polish steps to restore the flat surface. A literature survey was used to identify reliable etchants, and etching methods utilized on nickel alloys and summarized from various works [24][25][26][27][28] are shown in Table 2, encompassing both chemical and electrolytic etching methods. The etching time was incrementally increased for each etchant from a brief duration to establish a time step.…”
Section: Methodsmentioning
confidence: 99%
“…A comparative analysis was conducted to evaluate the grain size and carbide distribution between Ni600 and Ni625. Some previous studies have summarized and compared etchants for nickel alloys [24][25][26][27][28], but this paper aimed to systematically compare, more intuitively, the effects of several etchants effective on Ni600 and Ni625. Specifically, it focused on the morphologies they produce on the sample surfaces and their distinct impacts on carbides.…”
Section: Introductionmentioning
confidence: 99%